Configuration of robotics solutions in Microsoft robotics developer studio - Ho, Randy Pin Yan. (2010)
In today’s world, robotics is getting more ubiquitous. However, there is still a lack of a single software platform that can unify robotics. MRDS attempts to achieve that by conceptualizing the components of a robot as a distributed network of service interoperating together, fitting them into the services-oriented model paradigm. The project is to explore how MRDS achieves that and its practical implementation. Firstly, literature review is done on MRDS itself, as well as some well known SLAM techniques and path planning algorithms. After which, Kalman filtering is then implemented in MRDS. It continues with implementing A* algorithm. All are done in simulation. The project ends off with the discussion of the suitability of implementing solutions in MRDS, as well as its limitations. Recommendations are also made on how the project can be extended to different areas of development in the future.